Patterns of Semantic Memory Impairment in Mild Cognitive Impairment - Sven Joubert; Olivier Felician; Emmanuel J. Barbeau; Mira Didic; Michel Poncet; Mathieu Ceccaldi (Behavioural Neurology)
Although the semantic memory impairment has been largely documented in Alzheimer's disease, little is known about semantic memory in the preclinical phase of the disease (Mild Cognitive Impairment). The purpose of this study was to document the nature of semantic breakdown using a battery of tests assessing different aspects of conceptual knowledge: knowledge about common objects, famous people and famous public events. Results indicate that all domains of semantic memory were impaired in MCI individuals but knowledge about famous people and famous events was affected to a greater extent than knowledge about objects. This pattern of results suggests that conceptual entities with distinctive and unique properties may be more prone to semantic breakdown in MCI. In summary, results of this study support the view that genuine semantic deficits are present in MCI. It could be useful to investigate the etiological outcome of patients failing or succeeding at such tests.